2005
DOI: 10.1364/opex.13.005377
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Type I-IR and Type II-IR gratings with an ultrafast IR laser and a phase mask

Abstract: The formation of two grating types in SMF-28 fiber by focusing 125 fs, 0.5-2 mJ pulses through a phase mask onto a fiber sample is studied. The first type, specified as type I-IR, occurs below the damage threshold of the medium. The scaling behavior of the type I-IR gratings with field intensity and annealing properties suggests that their formation is related to nonlinear absorption processes, possibly resulting in color center formation. The second type, denoted as type II-IR, occurs coincidentally with whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
172
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(182 citation statements)
references
References 12 publications
3
172
0
Order By: Relevance
“…Fertein et al wrote LPG and operated them successfully at 1000°C [60]. These findings were confirmed for FBGs by various groups, both for direct [86] and phase mask written gratings [87][88][89][90][91]. Figure 5 depicts the reflectivity of conventional and femtosecond pulse written FBG at high temperatures [86].…”
Section: Annealing Propertiesmentioning
confidence: 70%
See 1 more Smart Citation
“…Fertein et al wrote LPG and operated them successfully at 1000°C [60]. These findings were confirmed for FBGs by various groups, both for direct [86] and phase mask written gratings [87][88][89][90][91]. Figure 5 depicts the reflectivity of conventional and femtosecond pulse written FBG at high temperatures [86].…”
Section: Annealing Propertiesmentioning
confidence: 70%
“…Reprinted with permission from [86]. 1000 • C. The small initial drop in reflectivity for the latter corresponds to the annealing of Type I modifications (e. g. color centers [41,87]). Thus, the remaining FBG is of Type II.…”
Section: Annealing Propertiesmentioning
confidence: 99%
“…26 The presence of additional near-edge absorption extends the apparent absorption edge tail and decreases MPI slope. In addition Smelser et al 27 have reported that the initial slope of the permanent refractive-index change writing kinetics in Ge-doped optical fibers follows an I 5 evolution with the laser intensity indicating a five photons absorption process. Then, due to a higher MPA coefficient …”
Section: Slope Changementioning
confidence: 99%
“…However the main region of interest justifying the use of these lasers is the Type II regime since changes in this regime are significantly more stable, up to 1000 ℃ [29,30]. Type II gratings written by using energies above T2 damage threshold [31] of the glass lead to very stable gratings.…”
Section: Application Of Femtosecond Lasersmentioning
confidence: 99%